Ontology Extraction Utilizing Augmented Direct Mapping for Movies Data Representation - May, Jiawei Wilson; Su, Cheng Haw; Subramaniam, Samini; Hassan, Muhsin; Saaid, Fatimah Almah (2018)
The volume of information is growing exponentially in today’s world. Nevertheless, the huge data are stored in various type of formats at various sizes and various growing rate.In addition, these data are heterogeneous and not directly consumable by the analytic tools. These resulted as one of the main challenges for data integration.In order to facilitate data integration, many mapping tools have emerged. In this paper, some recent mapping tools will be investigated, and the rules specified to acquire the ontology from relational databases will be proposed and discussed. Throughout the paper, we utilize the Internet Protocol television (IPTV) domain as the example to demonstrate the mapping of individual concepts of Relational Database (RDB) into ontology representation.